Perbandingan Rendemen, Skrining Fitokimia Dan Profil Kromatografi Lapis Tipis Ekstrak Etanol 96% dan Metanol Daun Sungkai (Peronema canescens Jack) - M. Andi Chandra; Hidayatullah, M. Hidayatullah; Putri, Putri Ermina Sari (Jurnal Kesehatan Islam : Islamic Health Journal, 2023)
Abstract. Kalimantan is rich in plants that are used as medicinal plants, one of which is the sungkai plant (Peronema canescens Jack). The aim of this research was to determine the comparison of yields of different solvent extracts and the comparison of phytochemical screening results and TLC profiles of 96% ethanol and methanol extracts. Extraction was carried out by maceration, then phytochemical screening and stain profiles were carried out using the thin layer chromatography (TLC) method using the mobile phase N-Hexane and Ethyl Acetate (8:2). The results of the research showed that the ratio of % yield of 96% ethanol extract was 8.87% and methanol was 8.85%. The results of phytochemical screening with 96% ethanol identified more secondary metabolites than maceration using methanol. The conclusion in this study is that the % yield ratio of ethanol extract is 96% greater than methanol extract. Phytochemical screening had more secondary metabolites in the 96% ethanol extract compared to methanol and TLC analysis of the 96% ethanol extract of sungkai leaves produced 5 stains with Rf values ​​of 0.06, 0.2, 0.25, 0.31 and 0.41, extract methanol produced 6 stains with Rf values ​​of 0.05, 0.13, 0.21, 0.25, 0.45 and 0.58. Kata Kunci: Sungkai (Peronemacanescens Jack,) TLC, 96% Ethanol Extract: Methanol